(untitled) (Bangladesh Journal of Medical Science, 2014)
Objective: To review the demographic, clinical and histomorphological aspects of xanthogranulomatous inflammation (XGI) in different organs. Material and methods: All the cases diagnosed as XGI by histopathology from the specimens received in the department of Pathology, Regional Institute of Medical Sciences, Imphal, Manipur, India over the period of 10 years from January 2001 to December 2010 were included in the study. All the available data including age, sex, organ of involvement, association with stone etc. were collected and analyzed retrospectively. All the slides were reviewed. The results were recorded and analyzed. Results: A total of 98 cases of XGI were diagnosed out of a total of 9755 specimens received, constituted by 5382 of gall bladder, 4298 of appendix, 41 of kidney and 24 of tube and tubo-ovarian mass making an overall incidence of 1%. The incidence of XGI in kidney was 12.19%, followed by 4.16% in tube and tubo-ovarian mass, 1.5% in gall bladder and 0.25% in appendix. Maximum number of cases were in the age group of 41-50 years with 33.67%. The female to male sex ratio was 2.5: 1. 90.2% cases in kidney and 86.6 % in gall bladder were associated with calculi. One case was associated with adenocarcinoma of gall bladder. Conclusion: Xanthogranulomatous inflammation which often mimics malignancy clinically and morphologically, is increasingly recognized in different anatomic locations. An accurate diagnosis will relieve the psychological panic of suspected malignancy and prevent the patient from aggressive treatment. DOI: http://dx.doi.org/10.3329/bjms.v13i3.16266 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.302-305